Core and modifiable components of academic detailing: demonstration of implementation strategy development, tailoring, and documentation process - Domlyn, Ariel M.; Hooks, Gwendolyn; Freitag, Michelle; Evans, Lacey; Stewart, Madison; Damschroder, Laura; Sussman, Jeremy B. (Frontiers in Health Services, 2025)
BackgroundAcademic Detailing (AD) is an educational outreach strategy that has shown positive effects on clinical practice, but its implementation varies widely across programs, necessitating consistent definitions of its essential components. The lack of standardized guidance for tailoring AD and other multi-component implementation strategies presents challenges in program development and effectiveness evaluation. To address this, we applied FRAME-IS (Framework for Reporting Adaptations and Modifications to Evidence-based Implementation Strategies) to specify AD's core components and demonstrate a repeatable program development process. By showcasing a multi-project, multi-site AD program, we aim to provide guidance for others in developing and tailoring AD programs, ultimately enabling more rigorous evaluations of AD's effectiveness.MethodsLiterature and training materials were reviewed to develop a list of common AD components, then organized according to a FRAME-IS template. Coders applied directed content analysis to materials from the MIDAS AD program, a multi-site implementation center using AD in four projects across the Veterans Health Administration. Tailoring and development of the AD program was coded according to FRAME-IS modules and ERIC strategy taxonomy.Results18 common AD components were identified. These components were retained but six were tailored and an additional seven were added across the MIDAS projects. The rationale for tailoring and additions was mostly to increase appropriateness, acceptability, adoption, and reach of AD. To assist in future tailoring of AD programs, we developed a list of generalizable guiding questions and an AD program documentation and tailoring template.ConclusionsAD is a robust strategy, but empirical study of the core and modifiable components is constrained by variable definitions of the components. This is the first attempt at developing documentation and tailoring guidelines for AD programs using the nomenclature of implementation science. We further suggest which components may be core and which may be modifiable. Our effort to specify AD components using the FRAME-IS method provides an example for other AD programs, contributing to the future use and study of AD as an implementation strategy and paving the way for more rigorous analysis of which modifications affect outcomes. Trial registration: ClinicalTrials.gov: NCT05065502.